Smart Boat Controller to Assist In Rescuing Flood Victims - Syed Khirudin, Sharifah Nor Atiqah; Muhammad Razif, Muhammad Rusydi; Sadun, Amirul Syafiq; Zaik, Muslim Abdullah (Progress in Engineering Application and Technology, 2023)
This project aims to improve the prototype version of Fahmi, Zhe C. H., and Nurul Nabilah's rescuing boat project. The main operating system will be similar in concept, with the boat able to avoid the obstacle automatically and providing the current location of the boat to the authorities. The distance between boat and obstacle will be detect using ultrasound sensor whereas the location will be provided by GPS.